3D composites of layered MoS2 and graphene nanoribbons for high performance lithium-ion battery anodes. Issue 34 (9th August 2016) - Tian, Ran; Wang, Weiqiang; Huang, Yaolin; Duan, Huanan; Guo, Yiping; Kang, Hongmei; Li, Hua; Liu, Hezhou
Abstract : 3D composites of layered MoS2 and interconnected graphene nanoribbons (GNRs) synthesized by a facile one-pot hydrothermal method exhibit excellent cycling stability and rate capacity. Abstract : 3D composites of layered MoS2 and interconnected graphene nanoribbons (GNRs) are synthesized by a facile one-pot hydrothermal method. During the synthesis process, the GNRs self-assemble into conductive bridges between the MoS2 layers to form 3D structures that exhibit large specific capacity, good cycling stability and rate capability. Specifically, the composites exhibit a specific capacity of 1009.4 mA h g −1 at 200 mA g −1 after 80 cycles of the cycling test. They also exhibit a specific capacity of 606.8 mA h g −1 at 3 A g −1 in the rate capability test. In comparison, the bare MoS2 nanoparticles exhibit a specific capacity of 139.8 mA h g −1 at 200 mA g −1 after 80 cycles of the cycling test and 37.4 mA h g −1 at 3 A g −1 in the rate capability test. The structure, morphology and chemical analysis show that the superiority of the 3D structure is due to the large surface area and abundant mesopores that render a high contact area between the electrode and electrolyte. Moreover, the synergistic effects between the 2D MoS2 layers and the 1D GNRs within the 3D structures enable fast Li ion and electron transportation, inhibit the self-aggregation of MoS2 nanosheets, and accommodate the volume expansion to gain cycling stability and rate capacity.